A novel community low-temperature district heat network with distributed generation as part of a multi-vector energy system - Jones, Sean (2019)
This work was conducted as part of project SCENIC (“Smart Controlled Energy Networks Integrated in Communities“) funded by the Energy Research Accelerator (ERA) and by extension Innovate UK.